Understanding the importance of social determinants and rurality for the long-term outcome after acute myocardial infarction: study protocol for a single-centre cohort study. Issue 4 (15th April 2022) - Sasko, Benjamin; Jaehn, Philipp; Müller, Rhea; Andresen, Henrike; Müters, Stephan; Holmberg, Christine; Ritter, Oliver; Pagonas, Nikolaos
Abstract : Introduction: Acute myocardial infarction (AMI) is a major public health issue in Germany with considerable regional differences in morbidity and mortality. Possible reasons for regional differences include a higher prevalence of cardiovascular risk factors, infrastructural deficits, different levels of healthcare quality or social determinants. We aim to study associations of social determinants and of rural infrastructure with the quality of medical care (eg, time to reperfusion or medication adherence) and on the long-term outcome after myocardial infarction. Methods and analysis: We will employ a prospective cohort study design. Patients who are admitted with AMI will be invited to participate. We aim to recruit a total of 1000 participants over the course of 5 years. Information on outpatient care prior to AMI, acute healthcare of AMI, healthcare-related environmental factors and social determinants will be collected. Baseline data will be assessed in interviews and from the electronic data system of the hospital. Follow-up will be conducted after an observation period of 1 year via patient interviews. The outcomes of interest are cardiac and all-cause mortality, changes in quality of life, changes in health status of heart failure, major adverse cardiovascular events and participation in rehabilitation programmes. Ethics and dissemination: Ethical approval was obtained from the Ethics Committee of Brandenburg Medical School (reference: E-01-20200923). Research findings will be disseminated and shared in different ways and include presenting at international and national conferences, publishing in peer-reviewed journals and facilitating dissemination workshops within local communities with patients and healthcare professionals. Trials registration number: DRKS00024463.